PENGARUH MEREK DAN PERSEPSI KUALITAS TERHADAP PERSEPSI NILAI SERTA DAMPAKNYA PADA NIAT UNTUK MEMBELI ULANG (Studi Empiris Pada Produk Agar-agarSwallow Globe Brand). - Agung Setyo Tjahjono, 12.42.02.0030 (Jurnal Mahasiswa Pasca Sarjana, 2014)
Swallow Globe Brand is the brand of agar-agar powder products in packaging sachet with Swallow bird logo and an image of a globe with a golden yellow color map of the world, wrapped in packaging dominant yellow color. The product is a market leader for this type of gelatin products. Due to increasing competition in emerging markets some gelatin products with the packaging and the drawings that resemble Swallow Globe Brand products. As stamp "Globe", where the Globe brand to market products under the brand names and logos that appear similar at first glance, but in fact when a very different look carefully. Many consumers are not aware of this difference. The purpose of this study to determine 1. brand / brand positive effect on the perception of value? 2.What positive influence on the perception of the quality of perception of value? 3. What brand has positive influence on purchase intentions re? 4. What positive influence on the perception of the quality of re-purchase intention? 5. Do perception and positive effect on the value of re-purchase intention? This research was conducted by survey method, by using a questionnaire to 100 respondents who at the time was making a purchase gelatin products being studied in Toko Sinar Mas Jl. Gang Baru no. 14, pasar Gang Baru Semarang. The questionnaire used to gather information about the brand, perceived quality, perepsi value, and re-purchase intention. The study concluded that Brand and Quality Perception Variables positive and significant impact on the perception of value, evidenced by tcount greater than t table and has a significance value smaller than 0.05. Varaibel brand and perceived quality positive and significant impact on Repeat Purchase Intentions, evidenced by the t-test value greater than pvalue and represents the strength of influence of brand variable to variable re-purchase intention. Furthermore, perception value and a significant positive effect on Repeat Purchase Intentions. Keywords: Brand, Quality Perception, Perception Value, Repeat Purchase Intentions.